Efficiency of Artistic Education: Praxiological Approach - Bularga Tatiana (Sciendo, 2021)
In our statements we proceed from the reality that the artistic activity differs much from other human activities through its ontological specifics, which requires taking into account the opportunities and challenges that arise in individual potential manifestation of the child, act that expresses by transposing the theoretical prescriptions into practical actions indisputable by the presence of emotional-affective reactions, by developing projects and logistical maps of action, is not waiting for certain stimuli coming from outside, but by enhancing the artistic intentions and decisions of child - subjects of education. In efforts to design the implementation process of innovative artistic praxeology we emerged from the assumption that TDA (teacher's didactic action) and PAA (pupil artistic action) become fundamental values of the integration of theory and praxeology in perspective of an effective education, provided that they be widely used both horizontally and vertically, according to the pentagonal model consisting of principles: proactivity, artistic intro-opening, creation/creativity, of success, re-conceptualizing and instrumented in modern theoretical and methodological perspectives.